2021
DOI: 10.1016/j.envpol.2021.117818
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on toxicity of SARS-CoV-2 peptides in aquatic biota: A study involving neotropical mosquito larvae (Diptera: Culicidae)

Abstract: Knowledge about how the COVID-19 pandemic can affect aquatic wildlife is still extremely limited, and no effect of SARS-CoV-2 or its structural constituents on invertebrate models has been reported so far. Thus, we investigated the presence of the 2019-new coronavirus in different urban wastewater samples and, later, evaluated the behavioral and biochemical effects of the exposure of Culex quinquefasciatus larvae to two SARS-CoV-2 spike protein peptides (PSPD-2002 and PSPD-2003) synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
0
6
1
Order By: Relevance
“…In our study, in particular, the hypothesis of the anticholinesterase effect observed in the brain of animals is a consequence of direct interactions between the PSPD-2002 and AChE is supported by molecular docking analysis ( Fig. 6 ), different from the findings of Charlie-Silva et al (2021) , Mendonça-Gomes et al (2021) and Malafaia et al (2022) , in which opposite effect (cholinesterasic stimulation) was observed in P. cuvieri tadpole, C. quinquefasciatus larvae and P. reticulata juveniles, respectively. In these studies, two possible mechanisms have been proposed for an increase in AChE activity.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…In our study, in particular, the hypothesis of the anticholinesterase effect observed in the brain of animals is a consequence of direct interactions between the PSPD-2002 and AChE is supported by molecular docking analysis ( Fig. 6 ), different from the findings of Charlie-Silva et al (2021) , Mendonça-Gomes et al (2021) and Malafaia et al (2022) , in which opposite effect (cholinesterasic stimulation) was observed in P. cuvieri tadpole, C. quinquefasciatus larvae and P. reticulata juveniles, respectively. In these studies, two possible mechanisms have been proposed for an increase in AChE activity.…”
Section: Discussioncontrasting
confidence: 47%
“…Initially, our data pointed to the absence of induction of hyper-/hypoactivity or anxiogenic-/anxiety-like behavior by exposure to PSPD-2002, which departs from the reported effects for C. quinquefasciatus larvae and P. reticulata juveniles exposed to the same peptides. In insects, aquatic exposure to PSPD-2002 (at 40 μg/L), for 48 h, induced a significant increase in the locomotor activity of larvae ( Mendonça-Gomes et al, 2021 ), and in fish, we demonstrated that although habituation learning has not been altered by the peptides (40 μg/L, 35 days exposure), the animals exposed exhibited anxiety-like behavior ( Malafaia et al, 2022 ). At the time, we evidenced a close relationship between the stimulation of the cholinergic system in animals exposed to peptides and the induction of reported behavioral changes, which was not observed in our study.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations